The Relationship between Comfort with Writing and Comfort Working with Numbers in STEM - Nicholes, Justin (Journal of Academic Writing, 2021)
Informed by writer-identity theory explaining links between emotion and identity, this study explores college STEM students’ feelings of comfort pertaining to math literacy, quantitative literacy, writing in STEM, and writing in general. Survey data from STEM majors (N = 134) was analyzed with Spearman rho tests of association. Results indicated that feelings of comfort working with numbers was significantly associated with comfort writing about numbers (rs = .504, p < .001); comfort writing about numbers was significantly associated with comfort writing in STEM (rs = .265, p = .002); and comfort writing in STEM was significantly associated with comfort writing in general (rs = .558, p < .001). This study suggests links between positive emotional experiences, which are implicated in identity performances, of quantitative writing, disciplinary writing, and writing in general. Future research on emotional experience and writer identity across the curriculum and in the disciplines is called for.